Language in Flight: Memorial, Narrative and History in David Copperfield - Cathy Caruth (Sillages Critiques)
This article addresses David Copperfield to try and understand what it means to write the autobiography of a violently traumatic life story. The traditional interpretation of the novel is to read it as representing, and overcoming, a childhood trauma through the linguistic mastery of the adult. Yet if the novel thus dramatizes how traumatic origins can be represented in writing, it also asks what it means for autobiographical language to originate in a trauma. In this sense the novel is not only about the orphan who becomes an autobiographer, but about the emergence of a literary language when the self can no longer tell its own story. What would it mean to read the novel as both the story of an orphan and as a literary, and traumatic, orphaned story?